Rasionalitas Tradisi Nyadran Masa Pandemi Masyarakat Kabupaten Sidoarjo - Fierla Dharma Kusuma (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2021)
Modern people have embedded with the rational character that leads to practical truth. The condition of society has connected within a network that did not cohesively measure by the surrounding structure. The identification of modernity has also considered the advancement of increasingly sophisticated human daily support tools. Sophistication offers an instant way to create independent social conditions. Tradition 'Nyadran' that still exists in the modern era especially in pandemic COVID-19, infest a paradoxical for a footing on a transcendental act. Nyadran has acculturated with the religious context is an attractive study of the complexity of modern society's lifestyle. This research aims to analyze the orientation and objective condition of implementing the Nyadran tradition that has been maintained in the community in Bluru Village, Sidoarjo. Rationality theory becomes the basis of research using the Verstehen method as a subjective assessment of the informants. The results found that the implementation of the Nyadran religious tradition in Bluru Village Sidoarjo is represented as an appreciation for the creation of a culture that corporated with the meaning of gratitude for God. A traditional value ​​is a part of the preservation of the predecessors with the historical linkages of the village.